Dental Caries and Tooth Wear in a Byzantine Paediatric Population (7th to 10th Centuries AD) from Yenikapi-Constantinople, Istanbul - Caglar, Esber; Gorgulu, Mehmet; Kuscu, Ozgur. (KARGER, 2016)
Dental caries and wear are important conditions to record in archaeological collections. The aim of the present paper is to determine the frequency and distribution of dental caries and dental wear in a mediaeval Byzantine paediatric population in Yenikapi, Constantinople, Istanbul. The present research was carried out on the skeletal remains of 1 infant and 28 children with a total of 180 teeth (113 primary and 67 permanent teeth). The frequency of ante-mortem tooth loss in the sample was 1%. The total frequency of carious lesions in the sample was 2.2%. The frequency of dental wear was rather low (3.3%) exhibiting presence of dentin clusters mostly. The present study evaluated an archaeological collection with low dental wear and low dental caries prevalence indicating a fishing community. (C) 2016 S. Karger AG, Basel
Keywords: Byzantine era; Children; Dental caries; Dental wear; Paediatric population; MEDIEVAL POPULATION; PERMANENT DENTITION; PREVALENCE; DISEASES; REMAINS; AGE; Dentistry, Oral Surgery & Medicine